Growth and differentiation factor 15 and NF‐κB expression in benign prostatic biopsies and risk of subsequent prostate cancer detection. (30th March 2021) - Rybicki, Benjamin A.; Sadasivan, Sudha M.; Chen, Yalei; Kravtsov, Oleksandr; Palangmonthip, Watchareepohn; Arora, Kanika; Gupta, Nilesh S.; Williamson, Sean; Bobbitt, Kevin; Chitale, Dhananjay A.; Tang, Deliang; Rundle, Andrew G.; et al.
ABSTRACT: Growth and differentiation factor 15 (GDF‐15), also known as macrophage inhibitory cytokine 1 (MIC‐1), may act as both a tumor suppressor and promotor and, by regulating NF‐κB and macrophage signaling, promote early prostate carcinogenesis. To determine whether expression of these two inflammation‐related proteins affect prostate cancer susceptibility, dual immunostaining of benign prostate biopsies for GDF‐15 and NF‐κB was done in a study of 503 case‐control pairs matched on date, age, and race, nested within a historical cohort of 10, 478 men. GDF‐15 and NF‐κB expression levels were positively correlated ( r  = 0.39; p  < 0.0001), and both were significantly lower in African American (AA) compared with White men. In adjusted models that included both markers, the odds ratio (OR) for NF‐κB expression was statistically significant, OR =0.87; p  = 0.03; 95% confidence interval (CI) =0.77–0.99, while GDF‐15 expression was associated with a nominally increased risk, OR =1.06; p  = 0.27; 95% CI =0.96–1.17. When modeling expression levels by quartiles, the highest quartile of NF‐κB expression was associated with almost a fifty percent reduction in prostate cancer risk (OR =0.51; p  = 0.03; 95% CI =0.29–0.92). In stratified models, NF‐κB had the strongest negative association with prostate cancer in non‐aggressive cases ( p  = 0.03), older men ( p  = 0.03), and in case‐control pairs with longer follow‐up ( p  = 0.02). Risk associated with GDF‐15 expression was best fit using nonlinear regression modeling where both first ( p  = 0.02) and second ( p  = 0.03) order GDF‐15 risk terms were associated with significantly increased risk. This modeling approach also revealed significantly increased risk associated with GDF‐15 expression for subsamples defined by AA race, aggressive disease, younger age, and in case‐control pairs with longer follow‐up. Therefore, although positively correlated in benign prostatic biopsies, NF‐κB and GDF‐15 expression appear to exert opposite effects on risk of prostate tumor development. Abstract : In benign prostate biopsies we found expression of GDF‐15 and NF‐κB were positively correlated and lower in African American compared with white men. Prostate cancer risk estimates, however, suggest that NF‐κB and GDF‐15 expression exert opposite effects on prostate tumor development.